THE EFFECT OF DIGITAL MARKETING ON CONSUMER PURCHASE INTENTION THROUGH BRAND TRUST AND CUSTOMER ENGAGEMENT: A SEM-PLS ANALYSIS OF FOOD-RELATED SMES IN PONTIANAK - Magdalena Depriyani (RADJA PUBLIKA, 2026)
Digital marketing transformation has changed how culinary MSMEs build relationships with consumers. This study aims to examine the effect of digital marketing on consumers’ purchase intention through brand trust and customer engagement in culinary MSMEs in Pontianak City. The study employed a quantitative approach with an explanatory survey design. A total of 285 respondents were selected using purposive sampling, consisting of consumers who had been exposed to digital promotions of culinary MSMEs and had made a purchase within the last six months. Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) with SmartPLS and a bootstrapping procedure of 5,000 subsamples. The results indicate that digital marketing has a positive and significant effect on brand trust, customer engagement, and purchase intention. Brand trust and customer engagement also have positive and significant effects on purchase intention. In addition, both variables significantly mediate the relationship between digital marketing and purchase intention, indicating a strong partial mediation pattern. These findings imply that the effectiveness of digital marketing in culinary MSMEs is determined not merely by promotional intensity, but more importantly by its ability to build brand trust and stimulate customer engagement. Practically, culinary MSME owners in Pontianak City need to develop digital strategies that are more interactive, informative, credible, and relationship-oriented in order to strengthen consumers’ purchase intention.